2017
DOI: 10.1534/g3.117.300209
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Stem Rust Resistance Allele in Durum Wheat that Exhibits Differential Reactions to Ug99 Isolates

Abstract: Wheat stem rust, caused by Puccinia graminis f. sp. tritici Eriks. & E. Henn, can incur yield losses in susceptible cultivars of durum wheat, Triticum turgidum ssp. durum (Desf.) Husnot. Although several durum cultivars possess the stem rust resistance gene Sr13, additional genes in durum wheat effective against emerging virulent races have not been described. Durum line 8155-B1 confers resistance against the P. graminis f. sp. tritici race TTKST, the variant race of the Ug99 race group with additional virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
1
36
1
Order By: Relevance
“…Previous mapping work with SNPs and SSR markers located TRTTF resistance on chromosome arm 6AS postulated as Sr8a (Bajgain et al., 2015a; Guerrero‐Chavez, Glover, Rouse, & Gonzalez‐Hernandez, 2015; Hiebert, Rouse, Nirmala, & Fetch, 2016; Nirmala et al., 2017). Similarly, in the current study, a strong association signal was detected on chromosome 6AS suggesting the involvement of Sr8a as it is the only major stem rust resistance gene present in bread wheat effective to TRTTF on chromosome arm 6AS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mapping work with SNPs and SSR markers located TRTTF resistance on chromosome arm 6AS postulated as Sr8a (Bajgain et al., 2015a; Guerrero‐Chavez, Glover, Rouse, & Gonzalez‐Hernandez, 2015; Hiebert, Rouse, Nirmala, & Fetch, 2016; Nirmala et al., 2017). Similarly, in the current study, a strong association signal was detected on chromosome 6AS suggesting the involvement of Sr8a as it is the only major stem rust resistance gene present in bread wheat effective to TRTTF on chromosome arm 6AS.…”
Section: Discussionmentioning
confidence: 99%
“…A number of resistance QTLs identified in the present study are coincident with chromosomal positions of previously reported Sr genes/QTLs based on both linkage and association mapping studies performed on tetraploid and hexaploid wheats. As an example, QTL region 16 on chromosome 6A, was previously identified in biparental populations by [34], and more recently in association mapping panel of durum wheat cultivars by [1,26]. For QTL region 10 on chromosome 4A (Table S1), loci for stem rust resistance were previously identified in both durum and bread wheat, and against several stem rust races, such as TTKSK [26,35,36], TKTTF [37], and TTTTF [38].…”
Section: Discussionmentioning
confidence: 99%
“…Five genes, namely Sr2 , Sr55 ( Lr67 / Yr46 / Pm46 ), Sr56 , Sr57 ( Lr34 / Yr18 / Pm38 ), and Sr58 ( Lr46 / Yr29 / Pm39 ), confer adult plant resistance (APR) ( Singh et al, 2015 ), and the 34 genes that impart all stage resistance (ASR) to Pgt race TTKSK are Sr9h , Sr13a , Sr13b , Sr15 , Sr21 , Sr22 , Sr24 , Sr25 , Sr26 , Sr27 , Sr28 , Sr32 , Sr33 , Sr35 , Sr36 , Sr37 , Sr39 , Sr40 , Sr42 , Sr44 , Sr45 , Sr46 , Sr47 , Sr50 , Sr51 , Sr52 , Sr53 , Sr59 , SrCad, SrTA10171 , SrTA10187 , SrTA1662 , SrTmp , and Sr1RS Amigo ( Jin and Singh, 2006 ; Jin et al, 2007 ; Faris et al, 2008 ; Hiebert et al, 2010 ; Kolmer et al, 2011 ; Liu et al, 2011a , b ; Qi et al, 2011 ; Rouse et al, 2011a , 2014 ; Rouse and Jin, 2011 ; Ghazvini et al, 2012 ; Olson et al, 2013a , b ; Bansal et al, 2014 ; Moore et al, 2015 ; Singh et al, 2015 ; Rahmatov et al, 2016 ; Zhang et al, 2017 ). Interestingly, Sr8155B1 does not confer resistance to race TTKSK, but does confer resistance to the more recent variants in the Ug99 race group ( Nirmala et al, 2017 ). Only a few resistance genes ( Sr2 , Sr13a , Sr13b , Sr25 , Sr26 , Sr57 , Sr58 , SrCad , SrTmp , SrND643 , Sr1RS Amigo , and Sr8155B1 ) were found to confer resistance in adapted germplasm ( Jin and Singh, 2006 ; Singh et al, 2008 , 2015 ; Njau et al, 2010 ; Hiebert et al, 2011 ; Basnet et al, 2015 ; Nirmala et al, 2017 ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sr8155B1 does not confer resistance to race TTKSK, but does confer resistance to the more recent variants in the Ug99 race group ( Nirmala et al, 2017 ). Only a few resistance genes ( Sr2 , Sr13a , Sr13b , Sr25 , Sr26 , Sr57 , Sr58 , SrCad , SrTmp , SrND643 , Sr1RS Amigo , and Sr8155B1 ) were found to confer resistance in adapted germplasm ( Jin and Singh, 2006 ; Singh et al, 2008 , 2015 ; Njau et al, 2010 ; Hiebert et al, 2011 ; Basnet et al, 2015 ; Nirmala et al, 2017 ; Zhang et al, 2017 ). The continuous search for new resistance sources and following through with their genetic characterization and strategic deployment is necessary for long-term control of the fast-evolving races of the stem rust fungus.…”
Section: Introductionmentioning
confidence: 99%